2004
DOI: 10.1124/dmd.32.7.762
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivation of Capecitabine in Human Liver: Involvement of the Cytosolic Enzyme on 5′-Deoxy-5-Fluorocytidine Formation

Abstract: ABSTRACT:Capecitabine, an anticancer prodrug, is thought to be biotransformed into active 5-fluorouracil (5-FU) by three enzymes. After oral administration, capecitabine is first metabolized to 5-deoxy-5-fluorocytidine (5-DFCR) by carboxylesterase (CES), then 5-DFCR is converted to 5-deoxy-5-fluorouridine (5-DFUR) by cytidine deaminase. 5-DFUR is activated to 5-FU by thymidine phosphorylase. Although high activities of drug metabolizing enzymes are expressed in human liver, the involvement of the liver in cape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 18 publications
1
41
0
Order By: Relevance
“…Human liver samples from 14 individual donors were supplied by the National Disease Research Interchange (Philadelphia, PA) through the Human and Animal Bridging Research Organization (Chiba, Japan), and those from 6 Japanese donors were obtained from autopsy materials that were discarded after pathological investigation (Izukawa et al, 2009). Microsomes were prepared as described previously (Tabata et al, 2004). The use of the human livers was approved by the ethics committees of Kanazawa University (Kanazawa, Japan) and Iwate Medical University (Morioka, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Human liver samples from 14 individual donors were supplied by the National Disease Research Interchange (Philadelphia, PA) through the Human and Animal Bridging Research Organization (Chiba, Japan), and those from 6 Japanese donors were obtained from autopsy materials that were discarded after pathological investigation (Izukawa et al, 2009). Microsomes were prepared as described previously (Tabata et al, 2004). The use of the human livers was approved by the ethics committees of Kanazawa University (Kanazawa, Japan) and Iwate Medical University (Morioka, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Human liver samples from nine donors were obtained from the Human and Animal Bridging Research Organization (Chiba, Japan), which is in partnership with the National Disease Research Interchange (Philadelphia, PA). Microsomes were prepared according to the method described previously (Tabata et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Because CESs were reported to be expressed in the inner lumen of the endoplasmic reticulum (Robbi and Beaufay, 1987;Medda and Proia, 1992), it was thought that only compounds located in the lumen underwent hydrolysis and glucuronidation. However, Tabata et al (2004a) reported that CES1 is present in both microsomes and cytosols and that cytosolic CES plays an important role in the bioactivation of the prodrug, capecitabine. Because there is approximately 5-fold more total cytosolic protein than microsomal protein, when we extrapolated this to the results obtained in the present study, we estimated that cytosolic MMF hydrolysis was equivalent to approximately 37 or 88% of the microsomal MMF hydrolysis.…”
Section: Kinetic Parameters Of Mmf Hydrolysis In S9 From Cos-1 Cells mentioning
confidence: 99%